Intentions to buy a service: The influence of service guarantees, general information and price information in advertising - C. Boshoff (South African Journal of Business Management, 2003)
Against the background of the challenge service marketers face in influencing the risk perceptions of service buyers, this study attempts to assess the impact three independent variables can have on potential service buyers’ intentions to buy a service. The three independent variables were: providing general service information; providing price information; and providing a service guarantee. The empirical study was of an experimental nature and used a factorial design to assess the impact of different mock advertisements on intentions to buy. The 18 different advertisements showed different combinations of information, prices and three levels of service guarantees. The empirical results indicate that combing all three of the independent variables (providing general service information, providing price information and providing a service guarantee) in printed advertising significantly enhances consumers’ intentions to buy. Another important finding of this study is that an unconditional service guarantee is not as important as is often suggested in the service literature.